2021
DOI: 10.1017/gmh.2021.15
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a lay counselor-delivered integrated maternal mental health and early childhood development group-based intervention in Northern Ghana: a cluster-randomized controlled trial

Abstract: Background Caregiver mental health is linked to early childhood development, yet more robust evidence of community-based interventions to prevent maternal depression and optimize socio-emotional development of young children is needed. Objectives of this cluster-randomized controlled trial (cRCT), based in Northern Ghana, are to assess the impact of the lay counselor-delivered, group-based Integrated Mothers and Babies Course and Early Childhood Development (iMBC/ECD) program on (1) the mental health of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Sub-group analyses in our study indicated that the iMBC/ECD program, relative to the control group, was associated with lowered depressive symptoms among specific sub-groups of women such as those with low levels of education and those with four or more children. A cluster-randomized controlled trial of iMBC/ECD implemented in Ghana also did not see overall significant effects but did see impacts on certain more vulnerable subgroups ( Baumgartner et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sub-group analyses in our study indicated that the iMBC/ECD program, relative to the control group, was associated with lowered depressive symptoms among specific sub-groups of women such as those with low levels of education and those with four or more children. A cluster-randomized controlled trial of iMBC/ECD implemented in Ghana also did not see overall significant effects but did see impacts on certain more vulnerable subgroups ( Baumgartner et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The main trial analysis did not find a significant mental health effect, although the results favored the intervention arm. Overall, there were very low depression means in both the intervention and control groups post-intervention; 1.96, 1.40, respectively [ 40 ]. Another possible explanation is that in contexts with significant gender inequitable norms, where women have less access to resources and economic opportunities, interventions focused on the relationship-level factors might be beneficial, but not sufficient unless structural-level factors are simultaneously addressed [ 56 ], such as the shared drivers of gender inequity and poverty suggested by the syndemics theory.…”
Section: Discussionmentioning
confidence: 99%
“…The cRCT was not blinded to participants, data collectors, and analysis team. More detailed information on sample size, randomization, and blinding is published elsewhere [ 40 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall prevalence of depression among mothers of young children ranges from 13% to 22% worldwide [ 41 , 42 ], and 23–55% of primary caregivers in developing countries have mental health symptoms [ 27 ]. In low- and middle-income countries, the average prevalence of women’s mental disorders is 19.8% postnatally [ 43 , 44 , 45 ], which means one in five women have post-partum depression [ 46 ]. In rural China, 39% of caregivers have at least one type of mental health issue [ 21 ], nearly 32% of caregivers suffer depressive symptoms, 42% suffer anxiety symptoms, and 30% suffer stress symptoms [ 47 ].…”
Section: Introductionmentioning
confidence: 99%